2013
DOI: 10.1371/journal.pone.0083261
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and Exogenous Hormone Factors in Relation to Risk of Meningioma in Women: A Meta-Analysis

Abstract: Background and ObjectiveA number of studies have focused on the association between oral contraceptive (OC), hormonal replacement therapy (HRT) and reproductive factors and meningioma risk, but the results were inconsistent. Thus, a meta-analysis was performed to obtain more precise estimates of risk.MethodsWe conducted a literature search using PubMed and EMBASE databases to July2013, without any limitations. Random effects models were used to summarize results.ResultsTwelve case-control and six cohort studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 56 publications
3
41
0
1
Order By: Relevance
“…Results for meningioma in previous meta-analyses 11,12 were broadly similar to ours, although the previous metaanalyses were based on fewer cases and did not report meningioma risk by type of HT preparation used. Our finding of a significantly increased risk of acoustic neuroma in women prescribed HT [RR 5 1.37 (95% CI 5 1.06-1.75)] is consistent with the only other report from a prospective study, the Million Women Study, where a significantly 4 Combining results from the current GPRD study and the Million Women Study also suggests greater risks in users of estrogen-only than estrogenprogestin HT, but the difference by HT type is not significant [summary RR 1.66 (95% CI 5 1.24-2.22) vs. 1.25 (95% CI 5 0.95-1.64), respectively, p heterogeneity 5 0.1].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Results for meningioma in previous meta-analyses 11,12 were broadly similar to ours, although the previous metaanalyses were based on fewer cases and did not report meningioma risk by type of HT preparation used. Our finding of a significantly increased risk of acoustic neuroma in women prescribed HT [RR 5 1.37 (95% CI 5 1.06-1.75)] is consistent with the only other report from a prospective study, the Million Women Study, where a significantly 4 Combining results from the current GPRD study and the Million Women Study also suggests greater risks in users of estrogen-only than estrogenprogestin HT, but the difference by HT type is not significant [summary RR 1.66 (95% CI 5 1.24-2.22) vs. 1.25 (95% CI 5 0.95-1.64), respectively, p heterogeneity 5 0.1].…”
Section: Discussionsupporting
confidence: 76%
“…[3][4][5][6][7][8][9][10][11][12][13] Evidence is limited by the lack of systematic reporting of findings for all CNS tumors combined, as well as by different tumor subtypes and by specific HT preparations. The findings for all CNS tumors combined are of public health relevance.…”
mentioning
confidence: 99%
“…Interestingly, the agreement of meningioma in parent-offspring pairs was modified by parents' sex and was significantly positive in mother-offspring pairs but not in father-offspring. These findings may be in line with some recent reports that suggest longer exposure to female sex hormones may increase the risk of sporadic meningioma in women [34]. Smith et al [35] reported that germline SMREC1 mutations predispose to familial meningioma with an incomplete penetrance in males in comparison with female family members and suggested the possibility of existing a hormonal stimulus to meningioma growth.…”
Section: Discussionsupporting
confidence: 89%
“…In: Proceedings of the 10th European Congress of Endocrinology, Berlin) first described the link between multiple meningiomas and prolonged treatment with CA in a series of nine women with tumor stabilization after treatment withdrawal. To date, there have been several reports of meningiomas associated with the long-term use of CA, and tumor shrinkage was also observed in some cases after discontinuation of the drug [2,8,21]. In addition, similar cases of meningiomas related to the long-term use of other progesterone agonists have been also reported [25,19,18,24,10] (Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…One explanation for this phenomenon is the increased use of postmenopausal hormone replacement therapy (HRT) [13]. However, epidemiological studies of the association between HRT and risk of meningioma have yielded conflicting results [21,5,14,4].…”
Section: Discussionmentioning
confidence: 99%